2018
DOI: 10.21041/ra.v9i1.374
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to compression and microstructure of concrete manufactured with supersulfated cements-based materials of volcanic origin exposed to a sulphate environment

Abstract: This research presents the results of concretes made with supersulfated cements (SSC) volcanic material bases. The concretes were cured under two regimes one for 24 h at 25 ° C and one for 22 h at 60 ° C and then at 25 ° C. The specimens were exposed to two conditions, dry under laboratory conditions and immersed in a solution with 3.5% CaSO 4 at 25 ° C for up to 180 days. After 180 days, the concrete with a 5% An-10% PC-10% CaO-75% PM cementant exposed to the CaSO4 solution achieved a compressive strength of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…The influence of the content of phosphogypsum waste on the compressive strength of concrete using super sulphated cement is presented in Figures 17 to 19. Experimental results showed that the 28-day compressive strengths of the SSCbased concrete can reach over 40 MPa, which can be found in previous studies [37,38]. The above results show that when the PG content increases or the slag content decreases, the strength of the concrete samples decreases.…”
Section: Effect Of Waste Phosphogypsum Content On Compressive Strengt...supporting
confidence: 84%
“…The influence of the content of phosphogypsum waste on the compressive strength of concrete using super sulphated cement is presented in Figures 17 to 19. Experimental results showed that the 28-day compressive strengths of the SSCbased concrete can reach over 40 MPa, which can be found in previous studies [37,38]. The above results show that when the PG content increases or the slag content decreases, the strength of the concrete samples decreases.…”
Section: Effect Of Waste Phosphogypsum Content On Compressive Strengt...supporting
confidence: 84%
“…aggregates used in concrete mixes are usually smaller than 40 mm. Aggregate that is larger than 40 mm in size is used for other civil works, for example for road works, earth retaining embankments, and others (Maldonado Bandala et al, 2018). Fine aggregate is usually called sand and coarse aggregate is called gravel, split, crushed stone, and others (Tomayahu, 2016).…”
Section: Aggregate Test Resultsmentioning
confidence: 99%